Identification of Potential Herbal Inhibitor of Acetylcholinesterase Associated Alzheimer’s Disorders Using Molecular Docking and Molecular Dynamics Simulation - Chandrabhan Seniya; Ghulam Jilani Khan; Kuldeep Uchadia (Biochemistry Research International)
Cholinesterase inhibitors (ChE-Is) are the standard for the therapy of AD associated disorders and are the only class of approved drugs by the Food and Drug Administration (FDA). Additionally, acetylcholinesterase (AChE) is the target for many Alzheimer’s dementia drugs which block the function of AChE but have some side effects. Therefore, in this paper, an attempt was made to elucidate cholinesterase inhibition potential of secondary metabolite from Cannabis plant which has negligible or no side effect. Molecular docking of 500 herbal compounds, against AChE, was performed using Autodock 4.2 as per the standard protocols. Molecular dynamics simulations have also been carried out to check stability of binding complex in water for 1000 ps. Our molecular docking and simulation have predicted high binding affinity of secondary metabolite (C28H34N2O6) to AChE. Further, molecular dynamics simulations for 1000 ps suggest that ligand interaction with the residues Asp72, Tyr70-121-334, and Phe288 of AChE, all of which fall under active site/subsite or binding pocket, might be critical for the inhibitory activity of AChE. This approach might be helpful to understand the selectivity of the given drug molecule in the treatment of Alzheimer's disease. The study provides evidence for consideration of C28H34N2O6 as a valuable small ligand molecule in treatment and prevention of AD associated disorders and further in vitro and in vivo investigations may prove its therapeutic potential.